2005
DOI: 10.1002/jqs.987
|View full text |Cite
|
Sign up to set email alerts
|

Holocene hydrologic variation at Lake Titicaca, Bolivia/Peru, and its relationship to North Atlantic climate variation

Abstract: Follow this and additional works at: http://digitalcommons.unl.edu/geosciencefacpub Part of the Earth Sciences CommonsThis Article is brought to you for free and open access by the Earth and Atmospheric Sciences, Department of at DigitalCommons@University of Nebraska -Lincoln. It has been accepted for inclusion in Papers in the Earth and Atmospheric Sciences by an authorized administrator of DigitalCommons@University of Nebraska -Lincoln.Baker, P. A.; Fritz, Sherilyn C.; Garland, J.; and Ekdahl, E., "Holocene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 47 publications
10
78
0
1
Order By: Relevance
“…On sub-orbital time-scales, several studies have shown that throughout the southern South American tropics, precipitation amount is elevated during North Atlantic cold events (Baker et al 2005). Again the speleothem records illustrate this best for the late Pleistocene.…”
Section: Precipitation In Tropical South America During the Late Quatmentioning
confidence: 86%
“…On sub-orbital time-scales, several studies have shown that throughout the southern South American tropics, precipitation amount is elevated during North Atlantic cold events (Baker et al 2005). Again the speleothem records illustrate this best for the late Pleistocene.…”
Section: Precipitation In Tropical South America During the Late Quatmentioning
confidence: 86%
“…For example, analysis of more than 80 yr of meteorological and historical records from Lake Titicaca in the tropical Andes demonstrates that lake level has varied ,7 m during the 20th century, with lake levels decreasing during El Niñ o events, rising with La Niñ a episodes, and varying on decadal time scales because of long-term changes in sea-surface temperature (SST) and resultant atmospheric linkages in the tropical North Atlantic Ocean (Baker et al 2001b). Importantly, sedimentary analyses demonstrate that past lake levels have been much more variable than at present, with historical changes of about 20 m occurring at centennial and millennial scales because of the effects of abrupt cooling of the high-latitude North Atlantic Ocean and its effects on SST gradients in tropics (Baker et al 2005). Even larger lake-level declines have resulted from variations in the South American summer monsoon driven by changes in orbital precession on 20,000-yr cycles (75 m) (Baker et al 2001a,b), and orbital eccentricities at scales of 100,000 yr (200 m) (Fritz et al 2007).…”
Section: Fossil Evidence Of Climate Effects On Lakesmentioning
confidence: 99%
“…Holzhauser et al (2005) compared glacier and lake level fluctuations in westcentral Europe over the last 3500 years and demonstrated synchronicity between glacier advances, periods of higher lake levels and maxima of atmospheric radiocarbon. There are numerous other examples of sediment and lake level data that point to a solar link (Baker et al, 2005;Morrill et al, 2006;Patterson et al, 2004;Stager et al, 2005;Verschuren et al, 2000;Wu et al, 2006;Haltia-Hovi et al, 2007).…”
Section: Analysis Of the Componentsmentioning
confidence: 99%